Defective double-strand DNA break repair and chromosomal translocations by MYC overexpression - Karlsson, Asa (National Academy of Sciences, 2003)
DNA repair mechanisms are essential for the maintenance of genomic integrity. Disruption of gene products responsible for DNA repair can result in chromosomal damage. Improperly repaired chromosomal damage can result in the loss of chromosomes or the generation of chromosomal deletions or translocations, which can lead to tumorigenesis. The MYC protooncogene is a transcription factor whose overexpression is frequently associated with human neoplasia. MYC has not been previously implicated in a role in DNA repair. Here we report that the overexpression of MYC disrupts the repair of double-strand DNA breaks, resulting in a several-magnitude increase in chromosomal breaks and translocations. We found that MYC inhibited the repair of γ irradiation DNA breaks in normal human cells and blocked the repair of a single double-strand break engineered to occur in an immortal cell line. By spectral karyotypic analysis, we found that MYC even within one cell division cycle resulted in a several-magnitude increase in the frequency of chromosomal breaks and translocations in normal human cells. Hence, MYC overexpression may be a previously undescribed example of a dominant mutator that may fuel tumorigenesis by inducing chromosomal damage.